2006
DOI: 10.1016/s0004-9514(06)70059-9
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of exercise therapy and manual mobilisation in acute ankle sprain and functional instability: A systematic review

Abstract: This study critically reviews the effectiveness of exercise therapy and manual mobilisation in acute ankle sprains and functional instability by conducting a systematic review of randomised controlled trials. Trials were searched electronically and manually from 1966 to March 2005. Randomised controlled trials that evaluated exercise therapy or manual mobilisation of the ankle joint with at least one clinically relevant outcome measure were included. Internal validity of the studies was independently assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
108
0
8

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(119 citation statements)
references
References 31 publications
3
108
0
8
Order By: Relevance
“…In a meta-analysis Van der Wees et al (2006) found a pooled relative risk of 0.38, which can be considered as a substantial clinical effect. After their review was written, two randomized controlled trials were published.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a meta-analysis Van der Wees et al (2006) found a pooled relative risk of 0.38, which can be considered as a substantial clinical effect. After their review was written, two randomized controlled trials were published.…”
Section: Introductionmentioning
confidence: 99%
“…a hip strategy) (Otten 1999). Although some studies showed beneficial effects of exercise programs on proprioceptive outcomes, like muscle reaction times (Hughes and Rochester 2008) and postural sway (Hughes and Rochester 2008), others found no evidence for an effect of rehabilitation programs on postural sway (van der Wees et al 2006). Moreover, both postural sway and muscle reaction time are characteristics that in addition to peripheral proprioceptive signals are dependent on an abundance of other variables.…”
Section: Introductionmentioning
confidence: 99%
“…Static stretching techniques may not be sufficient to address these arthrokinematic restrictions, justifying the use of talocrural joint mobilisations (Denegar et al, 2002). A Maitland anteroposterior (AP) glide of the talus within the mortise has been shown to lead to improvements in DF-ROM (Landrum et al, 2004;Van der Wees et al, 2006). Various treatment doses have been utilised by researchers in an attempt to study the effects of AP mobilisations of the talus on DF-ROM.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the literature reports positive therapeutic effects of balance training (e.g., single limb standing, standing on an ankle disc/wobble board) [29,4555] . However, there are a few studies that disagree with its treatment effect [56,57] . In the "Clinical Practice Guidelines" published in the Journal of Orthopaedic and Sports Physical Therapy, a panel of experts also concluded that the evidence is weak (grade of recommendation "C") on implementing weight bearing functional exercises and balance activities on unstable surfaces [18] .…”
Section: Rehabilitation For Ankle Sprainmentioning
confidence: 99%